1998
DOI: 10.1021/jm970862j
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibitors of Monoamine Oxidase (MAO). 5. 1-Substituted Phenoxathiin Inhibitors Containing No Nitrogen That Inhibit MAO A by Binding It to a Hydrophobic Site

Abstract: It is believed that a monoamine oxidase (MAO) inhibitor specific for MAO A, which is reversibly bound to this enzyme and displaceable by tyramine, will be an antidepressant which will not cause a rise in blood pressure when tyramine-containing foods are ingested. Some linear tricyclic compounds with a larger and a smaller group forming the central ring and with a lipophilic group ortho to the larger group (here mostly the SO2 function of phenoxathiin 10,10-dioxide) are reported to have the sought properties. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that tricyclic compounds such as xanthone ( 106 ) possess MAO-A-selective inhibitory properties (Figure ) ( , ). Further structural modifications afforded a series of phenoxathiin dioxides that retained MAO-A potency and selectivity observed with xanthones ( , ). BW 137OU87 ( 107 ) is one of the most potent and selective MAO-A inhibitors known with an in vitro K i = 10 nM and an in vivo ED 50 = 8 mg/kg ().…”
Section: Reversible Maoismentioning
confidence: 99%
“…Previous studies have shown that tricyclic compounds such as xanthone ( 106 ) possess MAO-A-selective inhibitory properties (Figure ) ( , ). Further structural modifications afforded a series of phenoxathiin dioxides that retained MAO-A potency and selectivity observed with xanthones ( , ). BW 137OU87 ( 107 ) is one of the most potent and selective MAO-A inhibitors known with an in vitro K i = 10 nM and an in vivo ED 50 = 8 mg/kg ().…”
Section: Reversible Maoismentioning
confidence: 99%
“…In the course of a drug discovery effort targeting phenoxathiin 10,10-dioxides as potential antidepressant agents, , we observed regiocontrolled formation of the 3,10-diisopropoxy derivative of 3 . Herein are described the details of this polycyclization and the X-ray crystal structure of the new ring system, which may be of interest to researchers in the field of organic charge-transfer complexes.…”
mentioning
confidence: 98%
“…8). The dataset of 65 compounds previously published [121,147,148] was divided in training set (52 compounds were used to generate the pharmacophoric model) and test set (13 compounds). Pharmacophore modeling was developed with the help of Maestro software [149] through Phase module [150] that combines conformational sampling with different scoring methods to identify pharmacophoric hypothesis.…”
Section: D Pharmacophoric Modelsmentioning
confidence: 99%